Nosemosis in africanized honey bee colonies in tropical conditions of Costa Rica: Nosema apis or Nosema cerenae - Calderón, Rafael A. (2021)
Calderón R. A., Sánchez L. (2021). Nosemosis in africanized honey bee colonies in tropical conditions of Costa Rica: Nosema apis or Nosema cerenae. Rev. Ciencias Veterinarias 39 (2): 1-8. https://doi.org/10.15359/rcv.39-2.3